Characterization and Antioxidant Activity Assay of Essential Oil Parts of Rosella (Hibiscus sabdariffa L.) - Helilusiatiningsih, Nunuk; Syahara, Muhammad Alwi; Irawati, Titik (The University of Lampung, 2024)
Rosella (Hibiscus sabdariffa L.) is known as a plant whose calyx contain high levels of antioxidant bioactive compounds and good inhibitory power against free radicals. However, other parts of the rosella plant have not yet been utilized for their antioxidant content and activity. The aim of this research is to compare the profiles of essential oils of parts of the rosella plant (seeds, leaves and flower petals) and their antioxidant activity. This research method begins with the process of extracting essential oils using the water-steam distillation method. Furthermore, the profile of the essential oil is known from the results of yield calculations and characterization using the GC-MS instrument. The antioxidant activity was tested using the DPPH method. The yield of essential oils obtained was 0.0107% for seeds, 0.0087% for leaves and 0.0136% for flower petals. GC-MS characterization shows that the most abundant chemical components contained in the essential oils of seeds, leaves, and flower petals are fatty acid compounds (2-propanoic acid, butanoic acid, hexanoic acid) and esters (neopentyl isobutyrate). The results of the antioxidant activity test showed the IC50 value for each essential oil, namely, seeds: 30.15 μg/ml, leaves: 171.27 μg/ml and flower petals: 126.58 μg/ml. The compound characteristics obtained showed the best results for rosella seed essential oil, this was supported by the fairly high antioxidant activity test results IC50 <50 μg/ml. Keywords: Antioxidant activity, Characterization, Essential oils, IC50, Yield.